Comparison of the effect of insecticides on three strains of Tyrophagus putrescentiae (Acari: Astigmata) using an impregnated filter paper test and a growth test - Stara, Jitka; Nesvorna, Marta; Hubert, Jan (Pest management science, 2014)
BACKGROUND: In this study, we compared the efficacy of insecticides against three strains of Tyrophagus putrescentiae using an impregnated filter paper test and a growth test. We tested the suppressive activity of commercial insecticides and their analytical standards (pirimiphos-methyl, cypermethrin, deltamethrin, chlorfenapyr, β-cyfluthrin). METHODS: The strains of T. putrescentiae originated from a laboratory, a field and dog food. The mortality of the mites due to active ingredients and analytical standards was tested using an impregnated filter paper test after 24 h. Lethal doses, LD50 , LD95 and LD99 were determined. A growth test was used to observe the suppressive effect of the active ingredients on mites at 21 days after application of the active ingredients to wheat grain. The effective doses ED50 , ED95 and ED99 were determined, indicating the concentration at which the population was reduced by 50, 95 and 99% more than control. RESULTS: Cypermethrin, β-cyfluthrin and a formulation of deltamethrin with piperonylbutoxide in the pesticide K-Othrine showed low toxicity to mites. High toxicity was observed for chlorfenapyr (LD50 : 0.1-1 µg cm(-2) ; ED50 : 0.11-1.2 µg g(-1) ) and pirimiphos-methyl (LD50 : 0.01-0.06 µg cm(-2) ; ED50 : 0.2-12 µg g(-1) ). We did not find significant differences among the compared strains in terms of their sensitivity to highly toxic insecticides. CONCLUSION: The obtained results showed that a filter paper test is a more sensitive method of identifying differences in pesticide susceptibility among strains, but the efficacy of pesticides against one species should be tested using a growth test.
Keywords: Acaricides; storage; grain; Animals; léková rezistence; mite; resistance; Toxicity Tests; control; Drug Resistance; zvířata; akaricidy; testy toxicity; pesticide; efficacy; Acaridae